Gambaran Pengetahuan, Sikap Dan Tindakan Masyarakat Serta Hubungannya Dengan Kejadian Demam Berdarah Dengue Di Kecamatan Pangandaran Kabupaten Ciamis - Mara Ipa (Loka Litbang Kesehatan Pangandaran, 2009)
Abstract. Ciamis district is dengue hemorrhagic fever (DHF) endemic area that significantly increased of number of cases on last three years period (2004-2006). This fact is a reason to conduct research that aimed to know a description a society’s knowledge, attitude and practice (KAP) and also to know relationships between that one with the occurrences of DHF. The research was designed using cross sectional study; 195 respondents was inter-viewed to know the level of society’s KAP. The final results of this research was showed that the respondent’s KASP is good but does not give impact on occurrences of DHF cases be-cause its practice was not done yet by societies in control DHF disease.